Nilai Ekonomi Tanaman Obat di Taman Nasional Danau Sentarum, Kalimantan Barat - Ginting, Thasia; Ismail, Ahyar; Simangunsong, Bintang (UI Scholars Hub, 2017)
Danau Sentarum National Park (DSNP) is a conservation area which has an important role in people’s lives and society Kapuas Hulu in West Kalimantan. The objective of this study was to estimate the value of medicinal plants in the area TNDS. Contingent Valuation Method (CVM) with a single bounded was use to determine the willingness to pay for medicine plants. Data collected through direct interviews with 90 local households in DSNP using a questionnaire. Data analysis was done with MS. Excel® and SPSS® statistical software. The results show the variable value of the bid, income, age, education, and knowledge of medicinal plants significantly a ect the value of WTP. The expected WTP is found between IDR50.354,22 to IDR72.312,44 per household per month.